Optimalisasi Produksi Cabai Merah di Kabupaten Bangka Tengah - Fournita Agustina; Nanang Wahyudin; Rati Purwasih (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2022)
The productivity of red chili in the Central Bangka Regency is still below its genetic potential, where the genetic potential of curly red chili per hectare is 200-220 quintals. This condition raises the assumption that the production of red chili in the Central Bangka Regency is not optimal. The purpose of farmers doing red chili production activities is to make a profit. Still, if the production of red chili is not optimal, it will affect the actual profits obtained by farmers. Therefore, it is important to research the optimization of red chili production in the Central Bangka Regency. This study aimed to analyze the effect of red chili production on the total cost of red chili farming and the optimal amount of red chili production by farmers in the Central Bangka Regency. The research method used is the survey method. The sampling method is simple random sampling with a sample of 34 people. The data analysis method used in this study uses inferential statistical methods. The formulation and objectives of the first research will be answered using the total cost function in cubic form. Furthermore, to answer the formulation and objectives of the second study, an analysis will be carried out using the abc formula (quadratic formula). The analysis results show that the amount of red chili production significantly affects production costs in red chili farming in Central Bangka Regency. Still, the amount of red chili production in Bangka Regency Middle is not optimal. So that farmers can achieve the optimal amount of red chili production, farmers should be able to use production inputs efficiently in their farming.